MODEL ENTREPRENURSE: TINJAUAN INTEGRATIF - Grace Fresania Kaparang; Anthony Stafford Pangemanan; Nova Lina Langingi (NUTRIX, 2022)
Abstract The unemployment rate of nurses is increasing and there are still many who adhere to the traditional perspective of the nursing profession as employees. This global competitive era, as well as this pandemic, requires out-of-the-box nurses who dare to open nursing practices as entrepreneurs in overcoming the rising of unemployment. The study attempted to investigate entrepreneurial nurse model with Whittemore and Knafl's integrative review design, analyzing the quality of the articles with the Alberta Heritage Foundation's QualSyst tool. The search strategy is with the keywords "perawat wirausaha" and "nurse entrepreneur", written in English and Indonesian, with articles published in the last 10 years. The results of an integrative review of five eligible articles resulted in an entreprenurse model. The entreprenurse model shows that the factors that influence entrepreneurship or entrepreneurial tendencies were starting from the student level (course period - urgency to get a job) and creativity. Then, departing from that, the identification of opportunities is carried out to become entreprenurse, however, there are also perceived barriers felt by the entreprenurses. Recommendations to the Faculty of Nursing to invest by providing opportunities for students to practice entrepreneurship in college and for nurse entrepreneurs to share their lived experiences that can provide insight into the identification of opportunities and how to overcome obstacles in entrepreneurship in the field of nursing. Keywords: entreprenurse, model Abstrak Angka pengangguran perawat semakin meningkat dan masih banyak yang menganut perspektif tradisional dari profesi keperawatan sebagai pegawai. Era kompetitif global dan juga pandemik ini, memerlukan perawat out-of-the-box yang berani membuka praktik keperawatan sebagai wirausahawan dalam mengatasi bertambahnya angka pengangguran. Studi ini mencoba menginvestigasi tren perawat wirausaha dengan desain tinjauan integratif Whittemore dan Knafl, menganalisis kualitas artikel dengan QualSyst tool dari Alberta Heritage Foundation. Strategi pencarian adalah dengan kata kunci “nurse entrepreneur” dan “perawat wirausaha”, berbahasa Inggris dan Indonesia, dengan artikel yang dipublikasi 10 tahun terakhir. Hasil tinjauan integratif dari lima artikel eligible menghasilkan model entreprenurse. Model entreprenurse menunjukkan bahwa faktor yang mempengaruhi kecenderungan wirausaha atau kewirausahaan yaitu dimulai dengan tingkat mahasiswa (course period - urgensi mencari pekerjaan) dan kreativitas. Kemudian, berangkat dari itu, ada identifikasi peluang dilakukan untuk menjadi entreprenurse, tapi ada juga persepsi hambatan yang dirasakan oleh entreprenurse. Rekomendasi pada Fakultas keperawatan untuk dapat berinvestasi dengan memberikan kesempatan kepada mahasiswa untuk praktek entrepreneurship di bangku kuliah dan kepada perawat wirausahawan untuk dapat berbagi pengalaman yang dapat memberikan wawasan mengenai identifikasi peluang dan cara mengatasi hambatan dalam kewirausahaan dalam bidang keperawatan. Kata Kunci: entreprenurse, model